The effect of educational intervention on nurses’ attitudes toward the importance of family-centered care in pediatric wards in Iran - Rostami, Forouzan; Syed Hassan, Syed Tajuddin; Yaghmai, Farideh; Ismaeil, Suriani; Suandi, Turiman (Electronic Physician, 2015)
Introduction: Family-centered care sustains the unity of the child’s and the family’s health. The aim of this study was to determine nurses’ attitudes toward parents’ participation in the care of their hospitalized children in Iran in 2015. Methods: In this experimental study, 200 pediatric nurses from hospitals affiliated with the Shaheed Beheshti University of Medical Sciences in Tehran were selected using the multi-stage, random-sampling method. Data were gathered using a questionnaire that covered demographic information and nurses’ attitudes. The questionnaire consisted of 31 items and was completed by the nurses in three stages: 1) before intervention (pretest), 2) immediately after intervention (post-test), and 3) three months after intervention (follow-up). The data were analyzed via SPSS software and using descriptive and analytical methods. Descriptive statistics, the Spearman Correlation Coefficient, and Repeated Measure Analysis (the Bonferroni method) were used to assess the data. Results: The results indicated that there was a significant increase in the mean score of attitude after intervention [M (pre) = 3.35%, M (post) = 3.97%, p < 0.001)]. Most of subjects had neutral attitudes toward family participation in their children’s care. There were no significant relationship between the nurses’ socio- demographic characteristics and their attitudes. Conclusion: The nurses’ attitudes toward the family’s participation in the care of their hospitalized children were moderate. The nurses’ attitudes should be improved by taking part in continuous training programs.